Bad Kitty vs Uncle Murray - Bruel, Nick (Square Fish New York, 2011)
Kitty's owners are taking a week off and leaving Kitty and Puppy at home. So who's going to watch them? Good ol' Uncle Murray, star of the Fun Facts feature of previous Kitty books - the guy you thought knew everything about cats. Think again! It isn't long before Uncle Murray is driven to near madness by shenanigans of epic proportions. -- From amazon.com